THE DYNAMICS OF THE SUBSTRATE RECOVERY OF WASTE DUMPS IN CALCARY MINING UNDER NATURAL REGENERATION - Lima, Marcelle Teodoro; Ribeiro, Admilson Irio [UNESP]; Teixeira Dias, Herly Carlos; Rosa, Alexandra Guidelli; Pires, Gustavo Trevizan; Tonello, Kelly Cristina (Univ Federal Lavras-ufla, 2018)
This study aimed to evaluate the dynamics of the physical and chemical recovery of the substrates of waste dumps of different ages undergoing natural regeneration, in a calcary mining in Salto de Pirapora - SF Brazil. Characterization of the vegetation, vegetation and physical and chemical cover of the substrates of the abandoned waste dumps since 1994 and 2013 and the soil of a native forest fragment adjacent to the mining was carried out. Twelve plots of 10 x 10m were allocated in each environment. It was verified that the soil cover rate with herbaceous, grassy, regenerating and litter of the sterile stacks are similar to the native forest fragment. The same was observed for the physical characterization of soil resistance to penetration, soil moisture content and relative light index. For the chemical characteristics, in all areas sampled there is aluminum deficiency which, consequently, presented low potential acidity and alkaline pH. The CEC of the substrates of the waste dumps presented values similar to the CEC of the native forest fragment, with abundance in some essential nutrients, indicating the possibility of vegetation development in the sterile stacks and the contribution of the natural regeneration to the substrates. Thus, the plant-soil relationship via natural regeneration in the sterile piles contributed to the improvement of the edaphic quality of the substrates over time, being a potential form of recovery in calcary mining. Thereby, the Fabaceae predominated on the waste dumps, especially Leucaena leucocephala, which, despite being an exotic species, is relevant for the current recovery stage of the substrates.
Keywords: Physical properties of soil; Leucaena leucocephala; Degraded areas